Strategi Pengelolaan Paduan Suara Perguruan Tinggi: Studi Kasus Paduan Suara Mahasiswa Universitas Palangkaraya - Susiana Puspawatie (Journal of Music Science, Technology, and Industry, 2019)
Universitas Palangkaraya Student Choir, Central Kalimantan, has won various achievements at some championships held locally and internationally. This student activity unit (unit kegiatan mahasiswa, UKM) has been established since 1996 and has changed its management department every year. The purpose of this study was to determine the management strategy of the choir that is managed in the student activity unit at the university. For this reason, the formulation of the problem proposed in this study is how to apply management strategies in the Universitas Palangkaraya Choir Student Activity Unit? The results showed that there were 14 important principles applied by the choir at Universitas Palangkaraya to maintain its sustainability and existence. Based on the SWOT analysis, UKM Choir of Palangkaraya University has strengths in the spirit of togetherness, fairness and honesty, as well as order and discipline.